2020
DOI: 10.1002/cam4.3210
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of KIAA1199 by miR‐486‐5p suppresses tumorigenesis in lung cancer

Abstract: The most common cancer on a global scale is lung cancer, while it is also the main reason for cancer-related death. 1,2 Nonsmall-cell lung cancer (NSCLC), mostly made up of adenocarcinoma or squamous cell carcinoma, accounts for more than 85% of lung cancers. 3 Despite the development in advanced therapies, such as molecularly targeted drugs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Here, we attempted to elucidate the role of KIAA1199 in tumorigenesis of EOC in our present study. It is reported that KIAA1199, a transmembrane protein, expressed in various types of malignant tumor (Liu et al, 2018;Tang et al, 2018;Wang et al, 2020;Zhai et al, 2020;Zhao et al, 2019). Some research data presented that KIAA1199 gene was highly expressed in malignant tumors and could play a major role in cell mortality of normal human cells, thus combating cell immortality and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we attempted to elucidate the role of KIAA1199 in tumorigenesis of EOC in our present study. It is reported that KIAA1199, a transmembrane protein, expressed in various types of malignant tumor (Liu et al, 2018;Tang et al, 2018;Wang et al, 2020;Zhai et al, 2020;Zhao et al, 2019). Some research data presented that KIAA1199 gene was highly expressed in malignant tumors and could play a major role in cell mortality of normal human cells, thus combating cell immortality and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the functions of miR-486 on osteogenesis. Previously, miR-486 have been known as a tumor suppressor and were found decreased in several cancers such as lung cancer, gastric adenocarcinoma and so on [29][30][31]. Apart from the effects in carcinogenesis, miR-486 is an important content in extracellular vehicles (EVs).…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis and real-time quantitative reverse transcription PCR (qRT-PCR) was performed as previously described [ 26 ]. The specific primers for target genes are listed in Additional file 2 : Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described [ 26 ]. The primary antibodies used in this study were anti-CPNE1 (ab155675) (Abcam, UK), anti-RACK1 (sc-17754) (Santa Cruz, USA), anti-pEGFR (Tyr1068) (1H12) (#3777), anti-EGFR (#4267), anti-pAKT (Ser473) (D9E) (#4060), anti-AKT (#4685), anti-pERK (Thr202/Tyr202) (D13.14.4E) (#4370), anti-ERK (#4695), and anti-β-actin (#3700) (Cell Signaling Technology, USA).…”
Section: Methodsmentioning
confidence: 99%